2013
DOI: 10.5301/ejo.5000340
|View full text |Cite
|
Sign up to set email alerts
|

Mean Platelet Volume in Pseudoexfoliation Syndrome and Glaucoma

Abstract: The MPV values in both groups with PEX were higher than those in the healthy group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
1
7
1
2
Order By: Relevance
“…The role of the MPV in differentiation between BD and recurrent oral aphthous ulcers was also investigated, but no evidence for the effectiveness of the MPV in such differentiation could be obtained 23. In a recent study, Türkçü et al examined the MPV in 36 BD patients with ocular findings and found no significant change 6. However, in a very recent study from Turkey, MPV and severity of BD were found to be correlated with each other 31.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the MPV in differentiation between BD and recurrent oral aphthous ulcers was also investigated, but no evidence for the effectiveness of the MPV in such differentiation could be obtained 23. In a recent study, Türkçü et al examined the MPV in 36 BD patients with ocular findings and found no significant change 6. However, in a very recent study from Turkey, MPV and severity of BD were found to be correlated with each other 31.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, a limited number of studies have attempted to identify an inflammatory marker which can predict uveitis. Türkçü et al reported that initially, mean platelet volume (MPV) was significantly lower in patients with active uveitis than in controls, but the significance disappeared over time 6,7…”
Section: Introductionmentioning
confidence: 99%
“…Özellikle tıkayıcı vasküler hastalıklarda ortalama trombosit hacmi (OTH) değerlerinin normal popülasyona göre daha yüksek olduğu çeşitli çalışmalarda bildirilmiştir [3,4]. Daha önceki çalışmalarımızda OTH değerlerinin retinal ven tıkanıklıkları [5], psödoeksfoliasyon sendromu [6] ve aktif oküler Behçet [7] [3,11]. Pulmoner emboli hastalarında erken dönem hastane mortalitesi için bir belirteç olabileceği de öne sürülmüştür [12].…”
Section: Introductionunclassified
“…Kliniğimizde gerçekleştirdiğimiz bir çalışmada psödoeksfoliasyonlu ve psödoeksfoliatif glokomlu olgularda OTH değerlerinin kontrol grubuna göre anlamlı olarak yüksek olduğunu saptadık [6]. Bu çalışmada OTH yüksekliğinin nedeni olarak psödoeksfoliatif materyalin endotelde birikimine bağlı endotel hücre yetmezliği neticesi oluşabileceği öne sürülmüştür [17].…”
Section: Introductionunclassified
“…Empirical evidence indicates that an increased mean platelet volume (MPV) is associated with several vascular diseases [27]. Also, the increased MPV is higher in subjects with XFM relative to the healthy controls [28]. Additionally, the platelet count (PLT) and MPV have high specificity and predictive value for platelet activity.…”
Section: Introductionmentioning
confidence: 99%